PERLINDUNGAN HUKUM DI RUANG SIBER: TELAAH YURIDIS ATAS RANCANGAN UNDANG-UNDANG KEAMANAN DAN KETAHANAN SIBER - Suharto; Dian Eka Kusuma Wardani; Ali Rahman; Muhammad Irwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
This study aims to analyze the legal framework of the Draft Law on Cybersecurity and Resilience (RUU KKS) in ensuring the protection of national strategic infrastructure and data, as well as to identify potential legal issues that may arise. The background of this research is driven by the growing threats of cybercrime in Indonesia, which have significant implications for national security, economic stability, and the protection of personal data. The research method employed is normative legal research using a conceptual approach and a statute approach. The data were collected from laws and regulations, academic literature, and relevant court decisions. The analysis technique used is qualitative descriptive, interpreting legal principles and assessing the coherence of existing regulations with the needs of national cybersecurity protection. The findings indicate that Indonesia’s current cybersecurity regulations remain fragmented across several sectoral laws, resulting in overlaps and weaknesses in ensuring legal certainty. The RUU KKS is expected to serve as a comprehensive legal instrument that strengthens the protection of critical infrastructure, prevents cyber misuse, and balances state interests with the protection of individual rights. Anchored in Pancasila and the 1945 Constitution, this regulation is essential to reinforce Indonesia’s digital sovereignty.